FAKTOR-FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN DENGAN CSR SEBAGAI VARIABEL MODERASI: IMPACT OF GOOD GOVERNANCE, FINANCIAL PERFORMANCE, AND FIRM SIZE ON FIRM VALUE WITH CORPORATE SOCIAL RESPONSIBILITY AS MODERATING VARIABELS - Dewi Tamara Rahmadhani; Saiful Anwar (Jurnal Proaksi, 2021)
One tool for measuring profits is the value of the company, because it can help executives and managers to succeed in managing the company's finances. Shareholders certainly want a high company value reflected in the high value of shares as well. Therefore, it is believed to be able to provide a high level of well-being to shareholders. The purpose of the research is to test and prove that CSR strengthens the factors of firm value in company basic industrial and chemical manufacturing listed on Indonesia Stock Exchange in 2015-2019. This research type uses a quantitative research approach. Sample determining method using purposive sampling on 71 manufacturing companies that publish annual report in 5-year study period. Technique data analysis using PLS (Partial Least Square) by Warp PLS software version 7.0. From hypothesis testing results, it’s concluded that GCG has no effect on firm value, financial performance has a significant positive effect on firm value, firm size has a significant negative effect on firm value, and CSR as variabel moderator showed unable to moderate the impact of GCG, financial performace, and firm size againt firm value. Keywords: GCG, ROA, Size, CSR, Tobins’Q